Early estimation of the wheat crop yield in irrigation district 038, RÃo Mayo, Sonora, México / Estimación temprana del rendimiento de la cosecha de trigo en el distrito de riego 038, RÃo Mayo, Sonora, México - Palacios-Vélez, Enrique; Palacios-Sánchez, Luis; Espinosa-Espinosa, José Luis (Tecnología y ciencias del agua, 2019)
In Irrigation District No. 38, RÃo Mayo, in the state of Sonora, México, wheat cultivation represents around 70 % of the area under irrigation (around 68,000 ha), so several studies have been performed with the aim of relating the crop yields with values of the NDVI index obtained from images by satellites Landsat 7, Landsat 8 and Deimos, as well as with estimations of evapotranspiration of the crops (ETc), evaluated through two methods, with the ETc = Kcb*ETr relation (ETr, Reference evapotranspiration), where Kcb is estimated as a function of the NVDI index, and through the MATRIC moisture balance method. Specifically, for the early estimation, a relationship between the yield and the value obtained with the NDVI index during the crop’s flowering has been considered, a time when it generally achieves its highest value and because there are enough antecedents in the literature, among them studies performed by the International Water Management Institute and "Colegio de Postgraduadosâ€, which stand out. However, this NDVI value is not enough for the estimation, so the value accumulated from heat units can be used, as will be shown in this article. On the other hand, in order to communicate the conditions of their crops to agricultural producers, Â viewers have been built, accessible through the Internet or local networks. Also, as part of the PLEIADeS and SIRIUS projects, financed by the European Commission, where the authors collaborate, the SPIDER viewer was created, which allows observing the NDVI and ETc values in each plot, although there are others, one designed by one of the authors and another by a doctoral student from Colegio de Postgraduados; the latter is installed in the Irrigation District. To calibrate the methodology proposed in estimating the probable yield, operations staff from the irrigation district performed measurements of the yields in several plots, with the objective of finding a function between the yields and the NDVI values during the crop’s flowering.